2023
DOI: 10.1037/mac0000072
|View full text |Cite
|
Sign up to set email alerts
|

Thinking first versus googling first: Preferences and consequences.

Abstract: On the internet, we can look up information that is not in one’s memory, but also information that is in one’s memory, but does not come immediately to mind. We become susceptible, therefore, to googling before trying to retrieve, which bypasses the benefits of “retrieval as a memory modifier” (Bjork, 1975), including that even a failed attempt to retrieve yet-to-be-learned information can potentiate learning of new information. Across four experiments, participants were asked to either generate answers to tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, this efficiency is not always beneficial. Recent research suggests that thinking about the answer to a question before using Google to obtain the answer leads to better retention of the answer in adults (Giebl et al., 2022). Given that children in this study believed that Google could more quickly answer questions, and they may see this as a benefit of using Google, it may be worthwhile to create educational interventions that encourage children to think before they type.…”
Section: Discussionmentioning
confidence: 99%
“…However, this efficiency is not always beneficial. Recent research suggests that thinking about the answer to a question before using Google to obtain the answer leads to better retention of the answer in adults (Giebl et al., 2022). Given that children in this study believed that Google could more quickly answer questions, and they may see this as a benefit of using Google, it may be worthwhile to create educational interventions that encourage children to think before they type.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Flanagin and Lew (2023) found that people overestimate their task performance if web-based information is available (see also Fisher & Oppenheimer, 2021). Another series of studies suggests that thinking about trivia questions before searching for the answers online improves later recall than immediately searching the Internet (Giebl et al, 2022). Importantly, reliance on Internet sources further increases the probability that one will rely on the Internet (Storm et al, 2017).…”
Section: Offloading In Everyday Lifementioning
confidence: 99%
“…While the nature of the processes underlying the benefits of pretesting is still being debated, it is fairly widely agreed that a major reason for this benefit is that pretesting leads students to think more deeply and critically about the information that was pretested when it is later encountered during the presentation of the tobe-learned material, resulting in a more elaborate encoding of such material. For example, even for questions to which students do not already know the correct answer, if they are required to search their memories for possible answers to such questions before being allowed to search for them on the Internet, they will remember the found answers better than if they had been allowed to search for them immediately (Giebl et al, 2021(Giebl et al, , 2022. Additionally, pretests can lead to a reduction in mind wandering (Pan et al, 2020) and enhance students' capacity to maintain focus during lessons (Pan & Sana, 2021).…”
Section: When Should We Give Tests?mentioning
confidence: 99%